Dual BRAF/MEK Blockade Restores CNS Responses in BRAF Mutant Erdheim Chester Disease Patients Following BRAF Inhibitor Monotherapy. Issue 2 (3rd March 2020) - Mazor, Roei D; Weissman, Ran; Luckman, Judith; Domachevsky, Liran; Diamond, Eli L; Abdel-Wahab, Omar; Shapira, Shirley; Hershkovitz-Rokah, Oshrat; Groshar, David; Shpilberg, Ofer
Abstract: Background: Erdheim Chester Disease (ECD), a rare inflammatory myeloid neoplasm, is known to be fundamentally reliant on the constitutive activation of the MAPK signaling pathway in the majority of patients. Consequently, inhibition of the V600E mutant BRAF kinase has proven to be a safe and efficacious long term therapeutic strategy for BRAF mutant ECD patients. Nevertheless, in a subset of patients with CNS disease, the efficacy of long term treatment may diminish, facilitating suboptimal responses or disease progression. Methods: We retrospectively describe three BRAF mutant ECD patients whose treatment with Vemurafenib was upgraded to Vemurafenib/Cobimetinib due to either disease progression, insufficient response or unacceptable toxicity. CNS response to therapy was evaluated using Magnetic Resonance Imaging (MRI) and extra-cranial disease was monitored using 18 F-Fludeoxyglucose Positron Emission Tomography / Computed Tomography (PET/CT). Results: Three patients with a mean age of 52.6 years were treated with Vemurafenib for a mean duration of 26.6 months (range: 6-52). Monotherapies were upgraded to Vemurafenib/Cobimetinib dual therapy. The combination therapy was administered for a mean duration of 21 months (range: 19-23). All patients exhibited clinical and neurological improvement. Regression of lesions on MRI was noted in two patients. Both patients characterized by a PET avid disease responded to the biological treatment regimen with complete metabolic remissions. Conclusion: Dual inhibition of BRAF and downstream MEK may be a safe and effective therapeutic strategy for BRAF mutant ECD patients for whom BRAF inhibitor therapy proved insufficient, and as such appropriate for the long-term management of CNS disease in ECD.